2020
DOI: 10.1002/cpa.21899
|View full text |Cite
|
Sign up to set email alerts
|

Maximum of the Characteristic Polynomial for a Random Permutation Matrix

Abstract: Let PN be a uniform random N × N permutation matrix and let χN(z) = det(zIN − PN) denote its characteristic polynomial. We prove a law of large numbers for the maximum modulus of χN on the unit circle, specifically, sup∣z∣=1∣χN()z∣=Nx0+o()1with probability tending to 1 as N → ∞, for a numerical constant x0 ≈ 0.652. The main idea of the proof is to uncover a logarithmic correlation structure for the distribution of (the logarithm of) χN, viewed as a random field on the circle, and to adapt a well‐known second‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For the (integer-valued) Discrete Gaussian model, it has been shown that the maximum is of logarithmic order [50]. There are also results for the maximum of the logarithm of the characteristic polynomial of certain random matrices, see for example [4,21,22,46]. Like these random matrix ensembles, the sine-Gordon model is closely related to a Coulomb gas type particle ensemble, but our point of view is completely different.…”
mentioning
confidence: 92%
“…For the (integer-valued) Discrete Gaussian model, it has been shown that the maximum is of logarithmic order [50]. There are also results for the maximum of the logarithm of the characteristic polynomial of certain random matrices, see for example [4,21,22,46]. Like these random matrix ensembles, the sine-Gordon model is closely related to a Coulomb gas type particle ensemble, but our point of view is completely different.…”
mentioning
confidence: 92%
“…For the characteristic polynomial of the GUE, as well as other Hermitian unitary invariant ensembles, the law of large numbers for the maximum of the absolute value of the characteristic polynomial was obtained in [33]. Cook and Zeitouni [16] also obtained a law of large numbers for the maximum of the characteristic polynomial for a random permutation matrix, in which case their result does not match with the prediction from Gaussian log-correlated field because of arithmetic effects. Finally, in the article [15] in preparation with Claeys, Fahs and Webb, we obtain the counterpart of Theorem 1.1 for the imaginary part of the characteristic polynomial of a large class of Hermitian unitary invariant ensembles.…”
Section: Comments On Theorem and Further Resultsmentioning
confidence: 99%
“…This is obtained by taking t = 1, s = λ + 1 and A = V N \V δ N in (25). The following lemma, which will be proved in Section 3, provides the upper bound for the left tail of the maximum restricted to a sub-box of V N .…”
Section: P(maxmentioning
confidence: 99%
“…For the counterpart progress on the Riemann zeta side, we refer the reader to [7,8,11]. For random permutation matrices, a law of large numbers result was obtained in [25].…”
Section: Introductionmentioning
confidence: 99%